Improvement of Typing Skills Through the Use of Rapid Typing Applications in Office Administration Education Students - Ramdani, Umrah; Darwis, Muh.; Nasrullah, Muh. (Pinisi Journal of Officers Review, 2025)
Students of the Office Administration Education Study Program need typing skills, especially in terms of accuracy and speed, so that they can perform academic tasks and administrative work. However, many students do not have this ability.  The aim of this study was to find out whether students' typing skills improved after using rapid typing applications, especially in terms of accuracy and speed.  This study employed a quantitative approach. This type of experimental research uses a pretest-posttest one-group design, or a research model that involves initial and final measurements of the same group without a control group.  The sample of this study consists of 35 students of the Office Administration Study Program, State University of Makassar, class of 2025.  Microsoft Excel and SPSS programs process data analysis using descriptive and inferential statistics.  The results of the study show that using the Rapid Typing application improves typing skills.  The results of the t-sequence sample test showed a significance value of 0.000 (p < 0.05), which showed a statistically significant difference between the pre-test and post-test results; the average typing speed increased from 15.66 words per minute (WPM) in the pre-test to 25.60 WPM in the post-test.  The normality tests of the Kolmogorov-Smirnov and Shapiro-Wilk indicated that the data showed a normal distribution.  Based on these findings, it can be concluded that fast typing apps can serve as an effective learning tool to improve students' typing skills, both in terms of accuracy and speed.